The Problem of Wage Policy in the Spring of 1947 - Slichter, Sumner H. (The Review of Economics and Statistics, 1947)
a whole rose 32 per cent.4 The smallest increase shown by any one of these industries was I4 per cent, and the maximum 49 per cent. The rise for the entire group was only 40 per cent of that for manufacturing workers. The increase for public school teachers was but io per cent from I939-40 to I942-43; for white collar employees in federal executive service, I5 per cent from I939 to 1943; for white collar employees of other governments, 9 per cent from I94I to I943.